A Critical Review of Biological Properties, Delivery Systems and Analytical/Bioanalytical Methods for Determination of Bevacizumab. (4th July 2021) - Filippo, Leonardo Delello Di; dos Santos, Karen Cristina; Hanck-Silva, Gilmar; de Lima, Felipe Tita; Gremião, Maria Palmira Daflon; Chorilli, Marlus
Abstract: Bevacizumab is a chimeric monoclonal human-murine antibody originated from murine monoclonal antibody (muMAb A4.6.1) with the human immunoglobulin IgG1. BVZ binds the extracellular portion of vascular endothelial growth factor receptors (VEGFR), which have tyrosine kinase activity. The mechanism of action of BVZ involves binding to VEGFR, Flt-1 (VEGFR-1) and KDR/Flk-1 (VEGFR-2), inducing homodimerization of two receptor subunits, and, consequently, autophosphorylation of their tyrosine kinase domains located inside the cytoplasm. With the advent of nanostructured systems it is increasingly necessary to look for safe analytical methods, ensuring the reliability of the results obtained by them, becoming essential to ensure the quality of medicines. In this work, the incorporation of bevacizumab in to different drug delivery systems was presented. Moreover, detailed investigation was performed about methods for qualitative and quantitative analyses of bevacizumab, including, biological fluids, and drug delivery systems, were investigated. Most recently high performance liquid chromatography coupled with various detectors, liquid chromatography, mass spectrometry and ELISA were used for this purpose. Thus, this review was performed to evaluate the benefits of bevacizumab carried by nanostructured systems and the analytical methods available for detection and quantification of these drugs.